FATORES DETERMINANTES DA DOR CRÔNICA E O PAPEL DA METILAÇÃO DO GENE NR3C1 - Branco, Alexandre Lima Castelo (2021)
Chronic pain is a multidimensional health condition with high prevalence in Brazil and its chronic condition may be related to depression and anxiety, diseases recognized as the most prevalent mental disorders in the world and major causes of functional incapacity, suffering and reduced quality of life. The relationship between depression, anxiety, pain, suffering and epigenetic alterations have already been described in the literature, but this relationship is not completely clear yet. Epigenetic alterations can affect gene expression and are related to the individual's adaptation to the environment in a relationship between genotype, phenotype and environment. The glucocorticoid receptor gene, NR3C1, is regulated by epigenetic mechanisms and acts to control the neuroendocrine axis via cortisol, which also links the gene to depression and other psychiatric illnesses. Thus, this research evaluated the determinants of chronic pain, biopsychosocial, biochemical and molecular factors in the epigenetic modifications of the NR3C1 gene in adults aged between 20 and 59 years, users of the Brazilian Unified Health System. The results of the biopsychosocial assessment in the sample showed a profile of people over 40 years old, with lower per capita income and education, low levels of cortisol, more reports of stress and anxiety, higher consumption of continuous medications, less physical activity and more prevalence of chronic pain. Pain was related to a statistical model that pointed out pain-related variables. Thus, the research showed indicators that point to a predominant profile of individuals with chronic pain, with determinant factors being: hypomethylation of the DNA of the NR3C1 gene in CpG 42, age over 40 years and low cortisol.